Advances in the study of extracellular vesicles of Naegleria fowleri and their role in contact-independent pathogenic mechanisms - Ismael Castelan-Ramírez; Catalina Flores-Maldonado; Dolores Hernández-Martínez; Lizbeth Salazar-Villatoro; Alberto Daniel Saucedo-Campos; David Segura-Cobos; Adolfo René Méndez-Cruz; Maritza Omaña-Molina (Parasites & Vectors)
Abstract Background Extracellular vesicles (EVs) are spherical membrane particles released by prokaryotic and eukaryotic cells. EVs produced by pathogenic organisms are known to play a role in host-pathogen interactions; however, despite some reports on Naegleria fowleri EVs, their potential role in inducing cytopathic effects remains poorly understood. In this study, we evaluated the role of N. fowleri EVs in contact-independent pathogenic mechanisms. Methods Extracellular vesicles were characterized via transmission electron microscopy, nanoparticle tracking analysis, SDS-PAGE, mass spectrometry, Western blotting, and zymography. EVs internalization by trophozoites and MDCK epithelial cells was also determined. Finally, mammalian cells were coincubated with EVs to evaluate haemolytic activity, epithelial paracellular ionic permeability alterations, and necrosis. Results Naegleria fowleri extracellular vesicles, ranging from 82.5 to 576.5 nm in size, were isolated, with a mean of 216.8 nm and a mode of 165.3 nm. Proteomic analysis identified 1006 proteins in the EVs, including leishmanolysin, a protein associated with pathogenic mechanisms such as adhesion and enzymatic processes. The proteolytic activity of EVs was found to be primarily due to serine protease. Furthermore, EVs were internalized by both trophozoites and MDCK cells. Additionally, EVs exhibited haemolytic activity in erythrocytes as well as increased ionic permeability and necrosis in MDCK cells 24 h postinteraction. Conclusions Naegleria fowleri EVs exhibit proteolytic and haemolytic activity and are internalized by trophozoites and MDCK epithelial cell monolayers, increasing the ionic permeability of the monolayer and inducing necrosis. Furthermore, these vesicles contain molecules associated with pathogenic processes such as leishmanolysin. Our results suggest that EVs facilitate paracellular invasion, migration, and damage caused by trophozoites and play a significant role in pathogenic processes as part of a contact-independent mechanism, which, in conjunction with a contact-dependent mechanism, enhances our understanding of the pathogenicity exhibited by this amphizoic amoeba during its invasion of target tissues. Graphical abstract